Pengaruh Model Pembelajaran Kooperatif Tipe Team Games Tournament terhadap Aktivitas Belajar Siswa pada Mata Pelajaran PAI - Hartono Hartono; Laila Badriyah (ISLAMIKA, 2023)
The Team Games Tournament type cooperative learning model implemented at Jati Agung Taman Sidoarjo High School has important value to study because it is effective, interesting and fun in learning, so that students do not get sleepy easily and do not feel bored during the learning process. Research objectives: 1) to determine the team games tournament type cooperative learning model at Jati Agung Taman Sidoarjo High School, 2) to determine student learning activities in PAI subjects at Jati Agung Taman Sidoarjo High School, 3) to determine the influence of the team games type cooperative learning model tournament for student learning activities in PAI subjects at Jati Agung Taman Sidoarjo High School. This research uses quantitative methods with percentage analysis and product moment correlation. The research population was 60 students. Data was collected through questionnaires, observation and documentation. The research results show that the use of the TGT model is considered good with a result of 61.83%. Student learning activities in PAI subjects were also assessed as good with a result of 61.33%. There is a positive influence of the TGT model on student learning activities in PAI subjects with a correlation coefficient rxy = 0.566, indicating a moderate influence.